La SIPSE: una società scientifica per la tutela, la conservazione e la valorizzazione del patrimonio storico-educativo - Anna Ascenzi; Elisabetta Patrizi (Studi sulla Formazione)
The article, starting from the analysis of the historical-educational heritage category, offers a state-of-the-art overview of the studies in this field and reconstructs the origins and functions of the Società Italiana per lo Studio del Patrimonio Storico-Educativo (SIPSE), born in 2017 in order to protect and enhance this heritage.